Smart Helmet for Motorcycle Safety Internet of Things Based - Matondang, Mhd Hafizh Azman; Asadel, Ahmad; Fauzan, Daris; Setiawan, Anwar Rudi (Tsabit Journal of Computer Science, 2024)
IoT (Internet of Things) is a concept that aims to utilize continuously connected internet connectivity, there are several IoT capabilities including data sharing, remote control and so on. One use that can be used is for security purposes, such as for safety riding , namely a Smart Helmet. The emergence of cases of motorbike theft and robbery requires vehicle owners to be more careful and increase their vigilance. Much has been done to prevent motorbike theft and robbery, for example using multiple locks and installing alarms on vehicles, but unfortunately some of these methods cannot completely overcome the rampant theft and robbery that is currently occurring. Apart from that, awareness among motorcyclists regarding the use of helmets is currently very minimal, which will have a fatal impact if the rider is involved in a high-profile accident without wearing a helmet. This thesis proposes a solution by developing a smart helmet, namely by providing facilities and equipment to anticipate crime while driving. Apart from that, this smart helmet will send a message if a robbery occurs and immediately send the driver's position. This helmet is integrated with the motorbike engine so the motorbike engine will stop if it is far from the helmet and the motorbike will not start if the helmet is not used. This Smart Helmet is designed based on IoT by using a Wireless module to connect to the motorbike engine, a GSM module for the alarm and notification system, and a GPS module to determine the location which is integrated with Google Maps.